Effectiveness of learning videos on language skills in learning Indonesia - Evi Sofia; Cepi Riyana (Inovasi Kurikulum, 2025)
Oral language skills are important in basic education, especially in learning Indonesia. Interactive learning, such as learning videos, educational applications, and interactive simulations, are expected to increase student engagement and facilitate mastery of language skills. This research examines the effectiveness of using learning videos in improving students' language skills in Indonesia. The research method used is a quantitative method with a quasi-experiment design. The research subjects were 63 grade V elementary school students in one of the schools in Bandung Regency. This research was divided into two groups consisting of 33 class Va students as the experimental group who used learning videos and 30 class Vb students as the control group who did not use learning videos. The data was collected through language skills tests before and after treatment, observation sheets, and student response questionnaires. The research showed that students who studied using instructional videos significantly improved their language skills compared to those without this media. These findings indicate that learning videos can be an effective alternative media for improving students' language skills in elementary schools.   Abstrak Keterampilan berbahasa lisan merupakan komponen penting dalam pendidikan dasar, khususnya dalam pembelajaran bahasa Indonesia. Pembelajaran interaktif seperti video pembelajaran, aplikasi edukasi, dan simulasi interaktif diharapkan dapat meningkatkan keterlibatan peserta didik dan memudahkan penguasaan keterampilan berbahasa. Penelitian ini bertujuan untuk mengkaji keefektifan penggunaan video pembelajaran dalam meningkatkan keterampilan berbahasa peserta didik pada pembelajaran Bahasa Indonesia. Metode penelitian yang digunakan adalah metode kuantitatif dengan desain eksperimen semu (quasi-experiment). Subjek penelitian yaitu peserta didik kelas V sekolah dasar di salah satu sekolah di Kabupaten Bandung sejumlah 63 peserta didik. Penelitian ini dibagi menjadi 2 kelompok yang terdiri dari peserta didik kelas Va sejumlah 33 peserta didik sebagai kelompok eksperimen yang menggunakan video pembelajaran dan peserta didik kelas Vb sejumlah 30 peserta didik sebagai kelompok kontrol yang tidak menggunakan video pembelajaran. Kemudian data dikumpulkan melalui tes keterampilan berbahasa sebelum dan sesudah perlakuan, lembar observasi, dan angket respons peserta didik. Hasil penelitian menunjukkan bahwa peserta didik yang belajar dengan menggunakan video pembelajaran menunjukkan peningkatan keterampilan berbahasa yang signifikan dibandingkan dengan peserta didik yang belajar tanpa media tersebut. Temuan ini menunjukkan bahwa video pembelajaran dapat menjadi alternatif media yang efektif dalam meningkatkan keterampilan berbahasa peserta didik di sekolah dasar. Kata kunci: keterampilan berbahasa; pembelajaran bahasa Indonesia; video pembelajaran